Phospholipid profile of different breast cancer cell lines - Dória, Maria Luísa Mouta Faria Lima (2012)
Breast cancer is the leading cause of cancer-related death in women. Altered cellular functions of cancer cells lead to uncontrolled cellular growth and morphological changes. Cellular biomembranes are intimately involved in the regulation of cell signaling; however, they remain largely understudied. Phospholipids are the main constituents of biological membranes and play important functional, structural and metabolic role. The aim of this work was to establish if phospholipids profiles of mouse and human mammary epithelial cells and breast cancer cells differ in relation to morphology and degree of differentiation. For this purpose, phospholipids of cell lines were analyzed using a lipidomic approach. Briefly phospholipids were extracted from six different cell lines (three from mouse and three from human) using Bligh and Dyer method, followed by a separation of phospholipid classes by thin layer chromatography. Phospholipid classes were quantified by phosphorus assay and analyzed by mass spectrometry. Important differences and similarities were found in the relative phospholipid content between mouse and human cells, between non-tumorigenic and cancer cells and between breast cancer cells with different levels of aggressiveness. Mass spectrometry and quantification analysis showed substantial alterations in the profile of sphingomyelin, cardiolipin and phosphatidylinositol classes comparing non-tumorigenic with cancer cells. Alterations in the most aggressive cell lines were observed in lysophosphatidylcholine, phosphatidylethanolamine and phosphatidic acid classes. Taken together, the results indicate that changes in phospholipid profile, either from mouse and human cell lines, can be associated to the difference in cell morphology, behavior and genetic expression, directly related to enzymatic and metabolic activities known to be altered in cancer. Thus, identification of phospholipid classes and their structure open new possibilities for exploration of such characteristics in cancer and provide novel biomarkers and disclose metabolic pathways with potential for therapy.